Social Enterprise As Commitment: A Roadmap - Alicia E. Plerhoples (Washington University Journal of Law & Policy, 2015)
At the nexus of law, business, and social justice there are a number of for-profit entities with underlying social missions. Such “hybrid” entities—low-profit limited liability companies, benefit limited liability companies, benefit corporations, public benefit corporations, and social purpose corporations—borrow principles from both the charitable and corporate sectors. Despite their hybrid nature these entities lack a clear accountability mechanism, putting such entities at risk of mismanagement, self-enrichment, and corporate waste. This Article presents a commitment approach to social enterprise governance within the bounds of existing social enterprise laws. Pherhoples argues that a commitment approach will facilitate an organization’s identity and foster a commitment that “reverberates through the entire organization.”
Keywords: entrepreneurship; social enterprise; benefit corporation; hybrid corporation